(untitled) (Analele Universității București.Filosofie, 2024)
Critical thinking has been a buzzword in both business and academic environments, as it represents the one of the greatest skillsets to possess for succeeding on a professional and personal level. This text argues for the idea that critical thinking today is a limited endeavor and that it is shaped by three philosophical assumptions that escape critical investigation: aporia allergy, part-time thinking, and Eurocentric Promethean thinking. The text highlights the importance of redesigning critical thinking without relying on these assumptions.